Moderating effect of social participation on the relationship between health status and depressive symptoms in older adults - Ow, Yvonne Su Yong; Wei, Chia-Shine; Li, Yang-Tzu (Frontiers in Public Health, 2025)
IntroductionDepression is a common mental health problem among older adults and a leading cause of disability worldwide. Health status and social participation has been found significantly associated with depression in older adults. However, the role of social participation in the relationship between health status and depression remains unclear. This study aims to investigate the relationship between health status and depressive symptoms in older adults and the moderating effect of social participation in the relationship.Materials and methodsA cross-sectional study with data from the National Health Interview Survey (NHIS) in 2013. Older adults aged 65 years or older were included in the study. Multiple regression analysis was performed to examine the relationship between health status and depressive symptoms and assess the moderating effect of social participation.ResultsOf the 2,731 participants, higher depressive symptoms were observed among older women, older adults who were single, living alone and having lower satisfaction on financial status. Regression analyses showed that activities of daily living (ADL) and instrumental activities of daily living (IADL) disability were positively associated with higher depressive symptoms. Perceived health status, cognitive functions and social participation were found negatively associated with depressive symptoms. A significant moderating effect of social participation between perceived health status and depressive symptoms was observed in this study.DiscussionThe findings highlight the role of social participation in moderating the effect of perceived health status on depressive symptoms and suggest that promoting social participation among older adults may be helpful for reducing depressive symptoms.